The Effect of Managerial Ownership, Company Growth, Profitability, and Investment Opportunity Set (IOS) On Accounting Conservatism - Abdul Goffar; Muhyarsyah Muhyarsyah (Budapest International Research and Critics University, 2022)
This study aims to prove and also analyze empirically the Effect of Managerial Ownership, Company Growth, Profitability, and Investment Opportunity Set (IOS) on Accounting Conservatism (Empirical Study on Manufacturing Companies on the Indonesia Stock Exchange for the Period 2017 – 2019). This research is based on secondary data obtained from the company's annual reports and annual financial statements. There are 72 companies out of a total of 186 companies in this study, which in selecting the sample used purposive sampling technique. As for the data processing in this study, using the data regression analysis method and processed with Microsoft Excel and Eviews 12 software. The results of research that has been carried out using panel data regression tests on the Fixed Effect Model prove that the managerial ownership variable has no significant effect on accounting conservatism, the company growth variable has a significant negative effect on accounting conservatism, the profitability variable has a significant negative effect on accounting conservatism, and the investment opportunity set variable. (IOS) has no significant effect on Accounting Conservatism.